Surface Lattice Resonances in 3D Chiral Metacrystals for Plasmonic Sensing. Issue 6 (27th December 2022) - Manoccio, Mariachiara; Tasco, Vittorianna; Todisco, Francesco; Passaseo, Adriana; Cuscuna, Massimo; Tarantini, Iolena; Gigli, Giuseppe; Esposito, Marco
Abstract: Chiral lattice modes are hybrid states arising from the chiral plasmonic particles assembled in ordered arrays with opportune periodicity. These resonances exhibit dependence on excitation handedness, and their observation in plasmonic lattices is strictly related to the chiroptical features of the fundamental plasmonic unit. Here, the emergence of chiral surface lattice resonances (c‐SLRs) is shown in properly engineered arrays of nanohelices (NHs), fully three dimensional (3D) chiral nano‐objects fabricated by focused ion beam processing. By tuning the relative weight of plasmonic and photonic components in the hybrid mode, the physical mechanism of strong diffractive coupling leading to the emergence of the lattice modes is analyzed, opening the way to the engineering of chiral plasmonic systems for sensing applications. In particular, a coupling regime is identified where the combination of a large intrinsic circular dichroism (CD) of the plasmonic resonance with a well‐defined balance between the photonic quality factor (Q factor) and the plasmonic field enhancement (M) maximizes the capability of the system to discriminate refractive index (RI) changes in the surrounding medium. The results lay the foundation for exploiting CD in plasmonic lattices to high performance refractometric sensing. Abstract : C‐SLRs are hybridized modes selectively excited by circularly polarization handedness, arising from the coupling between the diffractive orders (DOs) of the periodic lattice and the nanostructures plasmonic resonances. By tuning the lattice periodicity, and consequently the plasmonic/photonic fraction, it is possible to maximize the sensitivity to the RI surrounding environment changes, foreseeing novel highly sensitive detection schemes.